Biotransformation of dichlorodiphenyltrichloroethane in the benthic polychaete, Nereis succinea: Quantitative estimation by analyzing the partitioning of chemicals between gut fluid and lipid. (8th January 2015) - Wang, Fei; Pei, Yuan‐yuan; You, Jing
Abstract Biotransformation plays an important role in the bioaccumulation and toxicity of a chemical in biota. Dichlorodiphenyltrichloroethane (DDT) commonly co‐occurs with its metabolites (dichlorodiphenyldichloroethane [DDD] and dichlorodiphenyldichloroethylene [DDE]), in the environment; thus it is a challenge to accurately quantify the biotransformation rates of DDT and distinguish the sources of the accumulated metabolites in an organism. The present study describes a method developed to quantitatively analyze the biotransformation of p, p′‐DDT in the benthic polychaete, Nereis succinea. The lugworms were exposed to sediments spiked with DDT at various concentrations for 28 d. Degradation of DDT to DDD and DDE occurred in sediments during the aging period, and approximately two‐thirds of the DDT remained in the sediment. To calculate the biotransformation rates, residues of individual compounds measured in the bioaccumulation testing (after biotransformation) were compared with residues predicted by analyzing the partitioning of the parent and metabolite compounds between gut fluid and tissue lipid (before biotransformation). The results suggest that sediment ingestion rates decreased when DDT concentrations in sediment increased. Extensive biotransformation of DDT occurred in N. succinea, with 86% of DDT being metabolized to DDD and <2% being transformed to DDE. Of the DDD that accumulated in the lugworms, approximately 70% was the result of DDT biotransformation, and the remaining 30% was from direct uptake of sediment‐associated DDD. In addition, the biotransformation was not dependent on bulk sediment concentrations, but rather on bioaccessible concentrations of the chemicals in sediment, which were quantified by gut fluid extraction. The newly established method improved the accuracy of prediction of the bioaccumulation and toxicity of DDTs. Environ Toxicol Chem 2014;9999:1–9. © 2014 SETAC